Stabilization of democracy and world market-oriented modernization in Latin America: challenges for the 1990s - Sangmeister, Hartmut (Economics, 1996)
For Latin American economic recovery to result in sustained development, fundamental changes in traditional patterns of production, both in individual business and in the economy as a whole, are just as necessary as a change in patterns of social participation, because they are functional requirements of a combination of democracy, the market economy and the principle of a social state. (DSE/DÜI)
Keywords: Lateinamerika; Aufsatz in Zeitschrift